2018
DOI: 10.1371/journal.pone.0193957
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified colistin resistance genes, mcr-4 and mcr-5, from upper and lower alimentary tract of pigs and poultry in China

Abstract: Antimicrobial resistance against colistin has emerged worldwide threatening the efficacy of one of the last-resort antimicrobials used for the treatment of Enterobacteriaceae. To investigate the presence of the recently identified colistin resistance genes (mcr-4, mcr-5) in China, we established PCRs to detect mcr-4 and mcr-5 on 213 anal and 1,339 nasal swabs from apparently healthy pigs (n = 1,454) in nine provinces, and 1,696 cloacal and 1,647 oropharyngeal samples from poultry (n = 1,836) at live-bird marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 31 publications
1
32
1
2
Order By: Relevance
“…The P3 site appears to have particular characteristics in terms of the resistome. In addition to the genes already mentioned above (i.e., bla IMP , bla VIM and bla CTX−M ), other clinically relevant genes have also been detected at this site, such as mcr-5 genes, which confer resistance to colistin and which have recently been detected in plasmids from environmental, human and animal derived isolates (Sun et al, 2017;Tacão et al, 2017;Chen et al, 2018). Furthermore, in this site, the diversity of resistance genes found was superior to that of the other two sites (Supplementary Table S4).…”
Section: Analysis Of the Resistomementioning
confidence: 89%
“…The P3 site appears to have particular characteristics in terms of the resistome. In addition to the genes already mentioned above (i.e., bla IMP , bla VIM and bla CTX−M ), other clinically relevant genes have also been detected at this site, such as mcr-5 genes, which confer resistance to colistin and which have recently been detected in plasmids from environmental, human and animal derived isolates (Sun et al, 2017;Tacão et al, 2017;Chen et al, 2018). Furthermore, in this site, the diversity of resistance genes found was superior to that of the other two sites (Supplementary Table S4).…”
Section: Analysis Of the Resistomementioning
confidence: 89%
“…Generally, the high variation of mcr-5-carrying plasmids in only eight analyzed Salmonella isolates as well as the presence of Tn6452 in two of the host genomes indicate a high mcr-5 mobility, an independent acquisition of mcr-5-harboring plasmids by individual strains, and a successful integration in and adaptation to different genomic environments. This is supported by the increasing number of publications reporting the presence of mcr-5 in various bacterial species worldwide (10,(15)(16)(17)(18)(19)(20)(21)(22)(23). However, mcr-5 is only reported sporadically, and so far, no links can be made between isolates from the environment, livestock, food, and humans.…”
mentioning
confidence: 95%
“…In a concurrent study in Algeria and France, low prevalence and absence of mcr-1, respectively, was found in chickens (Chabou et al, 2016). In contrast, a Chinese study on chicken, duck and goose flocks not only reported high prevalence of the mcr-1 gene, but also identified for the first time the presence of all novel mcr genes (mcr-1 to mcr-5) in the examined poultry species (Zhang et al, 2018;Chen et al, 2018).…”
Section: Other Bacteriamentioning
confidence: 88%
“…Chromosomal mutations and other mcr genes seem to contribute as well. The recent discovery of all novel mcr genes in poultry (Zhang et al, 2018;Chen et al, 2018) and the development of a multiplex PCR protocol for their fast detection (Rebelo et al, 2018) prompt for surveillance of all mcr genes in future investigations. Furthermore, the higher prevalence of mcr-like genes when all Enterobacteriaceae are considered and the role of the "phantom resistome" should not be overlooked (Wang et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%